Production and decomposition of mangrove litter in the Waters of Kampung Bulang, Tanjungpinang City - Rumapea, Rahul; Lestari, Febrianti; Susiana, Susiana (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2025)
The process of litter decomposition plays an important role in producing important nutrients in the food chain and aquatic productivity of mangrove ecosystems. The purpose of this study is to determine the production of mangrove litter and its decomposition based on the density and cover of the mangrove canopy. The research location is in the waters of Bulang village. This research was carried out from June to July 2024. The method used is a systematic random method carried out in 20 sampling points. The research results found five species of mangroves, namely Rhizophora apiculata, Bruguiera cylindrica, Bruguiera gymnorrizha, Lumnitzera littorea, and Scyphiphora hydrophyllacea. The production of mangrove litter was 11.46 g DW/m² and the highest mangrove decomposition was 55.30%. The overall average density was 1195 individual/ha with medium criteria and the overall average canopy cover was 60.03% with moderate criteria. The results of the correlation test between litter production and canopy density and cover showed a very strong and significant correlation with litter production.